Implementation and Operational Research: Barriers and Facilitators to Combined ART Initiation in Pregnant Women With HIV. (1st May 2015) - Parker, Lucy A.; Jobanputra, Kiran; Okello, Velephi; Nhlangamandla, Mpumelelo; Mazibuko, Sikhathele; Kourline, Tatiana; Kerschberger, Bernhard; Pavlopoulos, Elias; Teck, Roger
Abstract : Background: In January 2013, Swaziland launched a prevention of mother-to-child transmission of HIV (PMTCT) B+ implementation study in rural Shiselweni. We aimed to identify patient and health service determinants of combined antiretroviral therapy (ART) initiation to help guide national implementation of PMTCT B+. Methods: This prospective cohort study uses routine data from registers and patient files in the PMTCT B+ pilot zone and a neighboring health zone where PMTCT A was the standard of care. All HIV-positive women not on combined ART at the first antenatal care visit between January 28, 2013 and December 31, 2013 were included. Results: 399 women from the PMTCT B+ zone and 183 from the PMTCT A zone are included. The overall proportion of women who had not started an antiretroviral intervention before 32 weeks' gestation was lower in the PMTCT A zone (13% vs 25%, P = 0.003), yet a higher proportion women with CD4 <350 initiated combined ART in the PMTCT B+ zone (86% vs 74%, P = 0.032). Within the PMTCT B+ pilot, initiation rates were highly variable between health facilities; while at patient level, ART initiation was significantly higher among women with CD4 <350 compared with CD4 >350 (80% vs 59%, P < 0.001). Among women with CD4 <350, those recorded as newly diagnosed were more likely to initiate combined ART. Although lower educational level and occupational barriers seemed to hinder combined ART initiation among women with CD4 >350, high proportions of missing socio-demographic data made it impossible to make any firm conclusions to this respect. Conclusions: This study not only demonstrates challenges in initiating pregnant women on ART, but also identifies opportunities offered by PMTCT B+ for improving treatment initiation among women with lower CD4 counts. Abstract : Supplemental Digital Content is Available in the Text.